Las espinacas de Sylvia - Pryor, Katherine; Raff, Anna (San Francisco, California : Readers to Eaters, 2019)
Sylvia Spivens refuses to eat spinach, but when the teacher gives her a package of spinach seeds for the class garden, she has no choice but to plant and nurture them.
Sylvia Spivens se niega a comer espinacas, pero cuando la maestra le da un paquete de semillas de espinacas para el jardin de la clase, no tiene mas remedio que plantarlas y nutrirlas.
In Spanish. En español.
Keywords: Spinach -- Juvenile fiction; Espinaca -- Novela juvenil; Vegetable gardening -- Juvenile fiction; Huertos -- Novela juvenil; Schools -- Juvenile fiction; Escuelas -- Novela juvenil; Food habits -- Juvenile fiction; Habitos alimenticios -- Novela juvenil